2020
DOI: 10.1080/13607863.2020.1740914
|View full text |Cite
|
Sign up to set email alerts
|

Dementia knowledge and its demographic correlates amongst informal dementia caregivers in Singapore

Abstract: Objectives: The Dementia Knowledge Assessment Scale (DKAS) is a validated assessment tool to measure dementia knowledge. However, the factor structure of the DKAS has yet to be validated in Singapore. This study aims to investigate the DKAS factor structure amongst a sample of informal dementia caregivers in Singapore, as well as their sociodemographic correlates. Methods: A total of 282 participants were evaluated on their knowledge of dementia by an interviewer administering the DKAS. Confirmatory factor ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 52 publications
4
14
0
Order By: Relevance
“…Another study [27] found a sample of Australian nurses, allied health professionals, care workers, and care managers had much higher dementia knowledge (mean score of 44.9 out of 54) compared to that of our study. However, our study result was similar with that of a study in which the sample of informal caregivers in Singapore had only moderate level of dementia knowledge with a mean score was 24.1 out of 46 [19].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Another study [27] found a sample of Australian nurses, allied health professionals, care workers, and care managers had much higher dementia knowledge (mean score of 44.9 out of 54) compared to that of our study. However, our study result was similar with that of a study in which the sample of informal caregivers in Singapore had only moderate level of dementia knowledge with a mean score was 24.1 out of 46 [19].…”
Section: Discussionsupporting
confidence: 89%
“…The differences of factor structure found in the studies might be due to differences in the sample. The majority of the samples in previous studies were nurses [15], health students and professionals in Japan [18], an international cohort of health professionals [16], and hospital and nursing home health care providers in China [17] except only one study from Singapore in which the sample was informal caregivers [19]. Our study specifically recruited only home care workers in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the first of its kind in Singapore to lend a voice to individuals of the general public to understand their perceptions on cognition and ageing, as previous studies on perceptions of cognitive health in Singapore were mainly quantitative or stakeholder focused (carers, healthcare professionals, policymakers) [17,[27][28][29][30]. Results are congruent with previous research demonstrating the lack of knowledge of dementia among the general public [17,27,31].…”
Section: Discussionsupporting
confidence: 81%
“…In all, 282 caregivers were recruited. More information about the study can be found in earlier articles [24][25][26].…”
Section: Participants and Proceduresmentioning
confidence: 99%